Scott and Bailey: How the Detective Drama reaches its Apogee in Light of the Historical Process. Issue 1 (2nd April 2016) - McKenna, Tony
Abstract : This article is about the ITV detective drama series Scott and Bailey . Following an analysis of its dramatic power, the author endeavours to situate Scott and Bailey in the context of crime drama more generally by offering a broader account of the development of the detective genre; from its 19th century origins in works by Poe and Conan Doyle, to Agatha Christie and Dorothy L. Sayers some decades later, right up to contemporary offerings such as Prime Suspect, Cracker and Scott and Bailey itself. The article aims to reveal the dialectical thread that runs through such a development. The archetype of the detective is transformed from its beginnings as an abstract, rootless creation, an ahistorical force of moral goodness and order—to an increasingly rounded and socially concrete figure grounded in an institutional hierarchy and subject to the social and class contradictions of the modern world. Coevally, the archetype is transformed from a character who is loosely upper class in behaviour and mannerism to a figure who is far more plebeian in social origin; the aesthetic dialectical that underpins the development of the detective archetype is one that involves a profound democratisation, then. In the conclusion, the author seeks to demonstrate how the democratisation of the aesthetic is part and parcel of the way emerging capitalism and the period of bourgeois revolutions which inaugurates it necessarily presuppose a higher level of participation in the political process on the part of the masses in and through the printing press, political propaganda, newspapers, etc. The article hopes to establish that the key to the aesthetic lies, in the last analysis, in the most thoroughgoing and profound democratisation of politics and culture at the level of the forms and structures of social being.